The Role of Learning Motivation as a Mediator in the Implementation of the Professional Mukmin Program in MARA Professional College on the Formation of Students ’ ‘Insaniah’ Leadership Character - Muda, Wan Mukhtar Wan; Zainol, Noor Azmi Mohd; Ghani, Sayuti Ab; Ismail, Amnah Saayah; M Z, Rosmiza (Journal of Asian Scientific Research, 2022)
Learning motivation is an important element in contributing to the effectiveness of the implementation of an educational program that shapes the character of students. A weak relationship of the elements of learning motivation will cause the objectives of the implementation of the program are not achieved. This study aims to measure the role of learning motivation as a mediator with all key elements of the implementation of the Professional Mukmin Program (PMP), namely PMP module content, the role of lecturers, management support and environmental support for the formation of ‘Insaniah’ leadership character of students in MARA Professional College. The study subjects consisted of 674 students in throughout Malaysia. Quantitative methods were implemented using the SmartPLS Path model. The results of the study confirmed the role of learning motivation as a mediator with all the key elements to the formation of students’ ‘Insaniah’ leadership character. The study also confirmed all the learning motivation hypotheses has a significant relationship with all key elements in contributing to the formation of students’ ‘Insaniah’ leadership character. The results of the study will be a guide in the evaluation of other elements that also contribute to the formation of the ‘Insaniah’ leadership character of students in MARA Professional College.